2014
DOI: 10.1167/iovs.13-13096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Age-Related Macular Degeneration in Korea: The Korea National Health and Nutrition Examination Survey 2010–2011

Abstract: The prevalence of AMD in Korea was similar to the prevalence of pooled Asian and Western populations. Age and serum GGT level were strongly associated with both the presence of any AMD and late AMD. Additionally, serum HDL level, HBsAg serum positivity, ever-smoking history, and systolic blood pressure were identified as risk factors for AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 42 publications
0
68
0
Order By: Relevance
“…Recently, Cho et al reported the prevalence of early-AMD (6.7%) and late-AMD (0.7%) in Korean representative population. 22,25 One unique strength of the present study is observation of the increase in prevalence over examination period. Prevalence of AMD in the study of Cho et al is slightly higher than that in the present study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, Cho et al reported the prevalence of early-AMD (6.7%) and late-AMD (0.7%) in Korean representative population. 22,25 One unique strength of the present study is observation of the increase in prevalence over examination period. Prevalence of AMD in the study of Cho et al is slightly higher than that in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…The results of previous major population-based studies are summarized in Table 6. [14][15][16][17][20][21][22][23][24][25] Age-specific prevalence data are meaningful in many ways. A further examination of our data reveals that age-specific prevalence of early-AMD in Korean adults exhibits different patterns from those of adults from other Asian and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several population-based studies on the prevalence of AMD have been performed in Asia. Prevalence estimates for early AMD and late AMD range from 2.5%–13.8% to 0.2%–7.0%, respectively, with higher prevalence in older study populations [3,11,12,13,14,15,16,17,18,19,20,21,22,23]. …”
Section: Epidemiologymentioning
confidence: 99%
“…Age is the most consistent risk factor for both early and late AMD, but may merely reflect the long latent period of the disease. Systemic risk factors that have been associated with increased risk of AMD in Asians include smoking [9,12,19,22,35,36], male gender [11,35], hypertension [12,15,21,35], hyperlipidemia [15], high levels of high density lipoprotein (HDL) [12,21], chronic kidney disease (CKD) [35], Hepatitis B surface antigen (HBsAg) positivity [12], liver cancer [37], coronary heart disease [19] and increased serum white blood cell levels. High levels of serum triglycerides [21], body mass index within the range of 24–28 [19] and alcohol consumption [13] were protective for early AMD while 25-hydroxyvitamin D (in males only) was protective for late AMD [38].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several previous studies reported the prevalence of early and late AMD in the Korea population using different time periods of the Korea National Health and Nutrition Examination Survey (KNHANES) [16][17][18]. The prevalence of early and late AMD ranged between 6.0% and 6.7% and between 0.6% and 0.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%